Produção das desigualdades socioespaciais em cidades médias Amazônicas: análise de Santarém e Marabá, Pará - Rodrigues, Jovenildo Cardoso [UNESP] (2015)
The city and Amazonian urban from this early twenty-first century are undergoing deep changes, associated with inherent determinations to the reproduction of capital in the urbanregional space, the advance of new economic agents, urbanization territorially selective, as well as the processes of urban restructuring and city restructuring, elements that have contributed to the production of socio-spatial inequalities. In the interpretation of these processes is essential to consider that urbanization induced by the state constitute condition for the expansion of economic frontier of capital in Brazilian and Amazon territory. At the local scale, medium-sized cities of Santarém and Marabá, from the 1990s, began to show deep and fast changes in their urban structures such as product expansion and intensification in the rhythm of the processes of urban restructuring and city restructuring, not always concomitant, as a mean for the expansion of the capital realization flows in the territory, and as a condition for reproduction of capital on a local scale. Taking into account the evidence presented, this thesis aims to understand, comparatively, how the production of socio-spatial inequalities in the cities of Santarém and Marabá in the early twenty-first century has been represented. In terms of features, as regards the medium-sized cities condition in the Amazon...